Socio-Cultural Transformation of Muhammadiyah and Nahdlatul Ulama Communities in East Java Prismatic Society - El-Rumi, Umiarso (Universitas Islam Negeri (UIN) Salatiga, 2022)
This research focuses on the socio-cultural transformation of Muhammadiyah and Nahdlatul Ulama’ (NU) communities in the prismatic communities of East Java (i.e., Jember, Bondowoso, and Lumajang). This condition cannot be separated from transforming various sectors in people’s lives that make it a prismatic (transitional) society. Therefore, this research seeks to find and understand the basic framework for the socio-cultural transformation of Muhammadiyah and NU communities in society. From the unit of analysis, this study uses a qualitative approach with ethnographic research, while the data collection techniques use in-depth interviews, participatory observations, field notes, and documentation. This research uses interactive data analysis by Miles, Huberman, and Saldana. This research finds that Muhammadiyah and NU communities have relatively different characteristics. In these three districts, members of Muhammadiyah and NU tend to be stagnant and unaffected by their various oppositional organizational doctrines. However, their socio-cultural transformation occurs triggered by external and internal factors dialectically related to themselves. The implication is that the modernist corporate identity attached to Muhammadiyah and the traditional community identity to NU is relatively irrelevant, especially when there is a progressive and alternating socio-cultural transformation between the two communities.